Can collaborative orientations strengthen or weaken effectiveness of improvisers’ emergency response to an emergency incident? A conditional process model - Tu JunMei; Xu Zhengquan (Frontiers in Psychology)
Due to insufficient information on the on-site emergency incident, respondents face a huge challenge to react effectively. This may suggest that the individual response to emergency tasks is likely to differ from that in daily work contexts. This study aims to explore the conditional process of how individuals’ improvisational cognitive appraisals (IICAs) in psychology affect their improvisational performance in an emergency setting and its consequences. Using the data garnered from the coal mine accident rescue teams we find that the level of IICAs positively impacts the individual’s improvisational ability to effectively respond to the emergency incident and the improvisational performance of temporary emergency teams as a whole. Further, an individual’s higher level of proclivity to seek cooperation with others in an emergency situation weakened the relationship between the individual’s improvisational cognitive appraisals and the individual’s improvisational performance team. Our work sheds light on how the improvisational performance of temporary emergency teams in a crisis setting is shaped, explaining why those who perform well in their day-to-day work often have difficulties in achieving the same good performance in a sudden crisis setting.